The restoration of pre-hispanic structures in the Huchuy Qosqo Archaeological Site - Yepez Peña, Miguel Angel (2021)
The purpose of the present study was the intervention of Restoration in the Pre-Hispanic Structures of the Archaeological Complex of Huchuy Qosqo, located in the District and Province of Calca, in Cusco City; as part of the exceptional testimony in its social, cultural and scientific value, showing the high degree of development of the Inca Culture in the different samples of geographical, topographical and magnitude of work management with the available technological resources. The intervention took a multidisciplinary approach, including the implementation of environmental and social safeguards, with the aim of resolving the problems identified in this archaeological complex. International documentation on heritage restoration and conservation was used as intervention criteria, resulting in the protection of the monument and the recovery of the original typology and spatial scheme, by means of restoration actions and the correct use of materials in the process. It is concluded that in order to guarantee the structural stability of the walls it is necessary to stop the causes of deterioration, by means of consolidation and restitution processes of the different structural components, as well as treatment with mineral consolidant and ethyl silicate in the adobe walls, being necessary the chemical protection and waterproofing of the mud plaster to avoid its degradation